Research progress of respiratory rehabilitation training in patients with stable chronic obstructive pulmonary disease (呼吸训练在慢性阻塞性肺疾病稳定期患者中的应用进展) - YANG Rui (杨蕊) (Association of Integrative Nursing, 2022)
As an important approach of rehabilitation, the respiratory rehabilitation training is effective to reduce the damage to the lung function and relieve the symptoms of respiratory disorder, thereby improving the quality of life and self-care ability of patients with stable chronic obstructive pulmonary disease. This paper summarized the research progress of respiratory rehabilitation training in patients with stable chronic obstructive pulmonary disease, and provided reference for the further research and clinical practice. (呼吸训练对促进慢性阻塞性肺疾病(COPD)稳定期患者康复具有重要作用, 呼吸训练能够在一定程度上减少患者肺功能受到的损伤, 减轻呼吸障碍症状, 从而提升患者的生活质量和自理能力。本研究针对COPD稳定期患者呼吸训练的研究进展进行综述, 旨在为相关工作提供有价值的参考。)